Effectiveness of multicomponent lower extremity injury prevention programmes in team-sport athletes: an umbrella - Brunner, R.; Friesenbichler, B.; Casartelli, N. C.; Bizzini, M.; Maffiuletti, N. A.; Niedermann, K. (British Journal of Sports Medicine, 2019)
Objective To identify which exercise combinations are most effective as part of a lower extremity injury prevention programme for team-sport athletes.